Analisis Perubahan Budaya Sekolah di SDN Tunjung Sekar 5 Malang - Sulton Maurobi; Aulia Azalia Nur Estiningtyas; Abil Abbas Baidhowi; Fina Nur Af’idah; Shobihatul Fitroh Noviyanti (IAINU Kebumen, 2026)
School culture is one of the important elements in shaping students’ character and behavior within the educational environment. This study aims to describe and analyze in depth the changes in school culture implemented at SDN Tunjung Sekar 5 Malang and their impact on students. This research employed a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The research data were obtained from teachers who were directly involved in the implementation of school culture changes. The results showed that changes in school culture were realized through various habituation activities, such as collective prayers, recitation of short surahs, congregational prayers, literacy activities, the Clean Friday program, and other religious activities. The implementation of cultural changes was carried out gradually by involving the principal, teachers, parents, and students. These habituation activities had a positive impact on students’ character development, particularly in terms of discipline, responsibility, religiosity, and politeness. However, the implementation of school culture changes still encountered several obstacles, such as the limited involvement of parents in assisting students at home and differences in students’ characteristics. Therefore, continuous collaboration between schools and families is needed so that the implementation of school culture can be carried out effectively and sustainably. This study indicates that habituation activities implemented consistently are able to support the establishment of a positive school culture at the elementary school level.